(untitled) (Journal of Pathology of Nepal, 2015)
BACKGROUND: Lymphadenopathy is a commonly encountered clinical problem. Fine needle aspiration cytology offers the alternative of an immediate, preliminary, although not always specific diagnosis with little trauma and cost, thus providing ample information for further management and reduce the amount of open biopsy. MATERIAL AND METHODS: FNAC was performed using 21 gauge needle attached with 10ml disposable needle. Slides were prepared, two were air dried and stained with field stain where as two were fixed in ethanol and was stained with PAP stain. One slide was stained with Ziehl-Neelson stain. Field and PAP stained slide were reviewed and diagnosed by Pathologist. RESULT: Out of the 225 patients, reactive lymphadenitis was the most common diagnosis (54.2%), followed by tubercular lymphadenitis (33.44%). Among the age group percentage of tubercular lymphadenitis was more in 210-30 years of age. Majority of the metastatic carcinoma was in cervical region, comprising mainly squamous cell carcinoma. CONCLUSION: Reactive lymphadenitis was the most common cause of lymphadenopathy especially in case of children. In case of older population, definite pathology for lymph node enlargement was found in most of the cases. Hence FNAC is warranted in lymphadenopathy, as it is simple yet of great diagnostic value.